Pengaruh Kepemimpinan Transformasional, Lingkungan Kerja Fisik dan Disiplin Kerja terhadap Kinerja Pegawai pada Perusahaan Daerah Air Minum (PDAM) Puruk Cahu - Kristiadi Kristiadi; Asmu’i Asmu’i; M. Hasanur Arifin (JURNAL BISNIS DAN PEMBANGUNAN, 2019)
PDAM Puruk Cahu district Moody highway is Companies engaged in the services the provision of clean water. One of them the purpose in the form of a PDAM is sufficient needs community will clean water , covering provision, development service means and infrastructure and distribution of clean water , medium aim others is come along and develop economy use support development area with expand field work , as well looking for profit as source main financing for area Research this aim for test influence Transformational Leadership (X1), Physical Working Environment (X2) and Work Discipline (X3) against Performance Employee (Y) on Regional Water Company (PDAM) Puruk Cahu sea way partial or simultaneously . Sample taken as much 24 employee using saturated sampling technique . Collecting data using questionnaire while analyst is using data Analysis Regression Multiple Linear through SPSS version 23 program . Results testing prove Trasnformasional Leadership significant effect on Employee Performance partially with big influence of 5,6%, Physical Work Environment significantly influence to Performance Employees partially with the influence of 48,7%, Work Discipline significantly influence Performance Employees partially with a large influence 41,1% while simultaneously Transformational Leadership, Physical Work Environment and Work Discipline has a significant effect on Employee Performance with a large influence of 73,6% including very strong category while the remaining 26,4% is influenced by other variables.  Keywords: Leadership Transformasional, Lingkaungan Physical Work, Work Discipline and Employee Performance